TECHNOLOGICAL INNOVATION AND ENVIRONMENTAL EDUCATION: A PLATFORM TO SUPPORT TEACHERS IN LESSON PLANNING TO ADDRESS THE CLIMATE CRISIS IN RS (Interdisciplinary Studies Journal, 2026)
This document presents the state of the art of a project aimed at developing an AI-Enabled Platform to address climate emergencies. It is an interdisciplinary proposal linked to the Doctoral Program in Informatics in Education (PPGIE/UFRGS), integrating Artificial Intelligence, Knowledge Graphs, and Nature-Based Solutions (NbS) to strengthen climate resilience in public schools located in vulnerable regions of Rio Grande do Sul, Brazil. Based on a critical literature review, the study highlights a gap in the articulation between emerging technologies and pedagogical practices focused on sustainability. The proposed platform aims to personalize learning pathways, generate climate simulations, and promote ecological microprojects within school contexts. The project's original contribution lies in its combination of technological innovation and place-based educational action, with potential impacts on public policies, teacher training, and socio-environmental transformation. The study emphasizes the importance of interdisciplinary solutions to address the climate crisis and outlines pathways for integrating education, data science, and environmental conservation.
Keywords: Artificial Intelligence; Environmental Education; Nature-Based Solutions; Knowledge Graphs; Informatics in Education